1987
DOI: 10.1159/000184098
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Corpuscular Nickel and Zinc in Chronic Hemodialysis Patients

Abstract: Serum and corpuscular nickel and zinc concentrations in 30 chronic hemodialysis patients were examined. Serum nickel and zinc levels before dialysis were 0.22 ± 0.03 μg/dl (normal value: 0.56 ± 0.08 μg/dl) and 70.0 ± 13.4 μg/dl (normal value: 96 ± 8 μg/dl) low, respectively. However, corpuscular nickel and zinc levels before dialysis were high: 1.25 ± 0.24 μg/dl (normal value: 0.88 ± 0.17 μg/dl) and 1,299 ± 146 μg/dl (normal value: 1,120 ± 80 μg/dl). Serum zinc levels significantly increased after dialysis, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…Indeed, several investigators [7,8,21,22] reported that high Al and Si levels cause bone diseases in chronic HD patients. Zn, Mn and Ni are essential trace elements for human nutrition [9,1116,[18][19][20]. In general, serum Zn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several investigators [7,8,21,22] reported that high Al and Si levels cause bone diseases in chronic HD patients. Zn, Mn and Ni are essential trace elements for human nutrition [9,1116,[18][19][20]. In general, serum Zn.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others reported that abnormalities of aluminum [1][2][3][4], silicon [5][6][7][8], zinc [9][10][11][12], manganese [13][14][15][16] and nickel [17][18][19][20] caused various kinds of compli cations in chronic hemodialysis (HD) patients. Elevated serum Al levels in chronic HD patients [1][2][3][4] were asso ciated with encephalopathy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other papers reported normal [20] or low nickel levels in serum of HD patients [22,23]. Dialysis fluid may be a source of increased serum nickel [36] which may then accumulate in bone and tissues of ESRD patients [97].…”
Section: Nickelmentioning
confidence: 94%
“…The erythrocyte Zn concentration in patients with chronic renal failure (CRF) was reported to be low [8], normal (3 papers) [17], but more often increased [18,19,22,29]. High erythrocyte Zn in the presence of low plasma Zn in patients with renal failure is probably in relation to the activity of the major Zn-containing erythrocyte enzyme carbonic anhydrase.…”
Section: Zincmentioning
confidence: 99%
“…The zinc metabolism is altered in chronic uremia, and it is not corrected by maintenance dialysis therapy [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. Zinc supplementation has been shown to improve some abnormalities in uremic patients [8, 9, 10, 17].…”
Section: Introductionmentioning
confidence: 99%